Generalized adding machines and Julia sets - Messaoudi, Ali [UNESP]; Valle, Glauco (Elsevier B.V., 2016)
We define stochastic adding machines based on Cantor Systems of numeration. Our aim here is to compute the parts of spectra of the transition operators associated with these stochastic adding machines in different classical Banach spaces. We show that these spectra are connected to fibered Julia sets. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.